Tongkonan Tongkonan: Symbol of Interfaith Peace in Tana Toraja, South Sulawesi - Saudi, Muammar (Satya Widya: Jurnal Studi Agama, 2025)
This article describes the portrait of interfaith peace in Toraja, South Sulawesi, which involves three religions: Christianity, Islam, and Indigenous. The aim is to explain structural and cultural conditions that include shared values or identity, the role of elite religious leaders, and community involvement. This study uses a qualitative method with a literature review approach that relies on journal, magazine, and news data. This study focuses on how interfaith residents in Tana Toraja can live together in peaceful conditions. What social changes threaten the culture of peace, and how to strengthen or reproduce the culture of peace?. The study results show a culture of peace in Toraja through community involvement in religious activities between different religions. Shared values through the existence of a Tongkonan (Toraja traditional house), a shared home for families of different religions. The role of elite leaders (traditional and religious) in controlling the dynamics in inter-faith relations. Also, economic relations between religions are obtained through their cultural diversity. This article also suggests the importance of reproducing family values as the principal value in caring for a culture of peace in Tana Toraja. Lastly, order the leluhut "siangga, sikamali na siangkarran " (mutual respect, longing for each other, and helping each other) can consistently be implemented in everyday life.